2018
DOI: 10.1016/j.anihpc.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Minnaert resonances for acoustic waves in bubbly media

Abstract: Through the application of layer potential techniques and Gohberg-Sigal theory we derive an original formula for the Minnaert resonance frequencies of arbitrarily shaped bubbles. We also provide a mathematical justification for the monopole approximation of scattering of acoustic waves by bubbles at their Minnaert resonant frequency. Our results are complemented by several numerical examples which serve to validate our formula in two dimensions.Mathematics Subject Classification (MSC2000): 35R30, 35C20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 83 publications
(145 citation statements)
references
References 36 publications
3
136
0
Order By: Relevance
“…satisfying the Sommerfeld radiation condition) fundamental solution to the Helmholtz operator ∆ + ω 2 in R 2 [55]. The value of this approach is that solving (2.4) is reduced to finding φ, ψ such that the two transmission conditions on ∂D hold [37,54]. An asymptotic analysis of the resonant frequencies and eigenmodes, based on their layerpotential representations (2.6), was performed in [13].…”
Section: Layer-potential Approachmentioning
confidence: 99%
“…satisfying the Sommerfeld radiation condition) fundamental solution to the Helmholtz operator ∆ + ω 2 in R 2 [55]. The value of this approach is that solving (2.4) is reduced to finding φ, ψ such that the two transmission conditions on ∂D hold [37,54]. An asymptotic analysis of the resonant frequencies and eigenmodes, based on their layerpotential representations (2.6), was performed in [13].…”
Section: Layer-potential Approachmentioning
confidence: 99%
“…|s−s ′ | ·ν s ′ ds ′ ds and define ω 2 M := 8π k l (ρ l −ρ0)Â l . The constant ω M is an approximation of the real part of the Minnaert resonance created by each bubble, see [2,6]. To simplify the exposition of our results in our ongoing work, all the bubbles are assumed to be identical in shape, and have the same density and bulk modulus.…”
Section: Background and Notationsmentioning
confidence: 99%
“…We now recall from e.g. [2,3] the main result that will allow us to understand the leading order behaviour of A in (9).…”
Section: Preliminariesmentioning
confidence: 99%
“…Here, we estimate the appropriate material parameters for the system of subwavelength resonators used in our version of the model from [10]. In particular, using physical values for the cochlea and representations of subwavelength acoustic resonators as harmonic oscillators, we estimate the appropriate value for the bulk modulus contrast µ, defined in (2). In [10] it is shown that a suitable approximation to basilar membrane motion can be achieved by considering an array of masses on springs.…”
Section: A Materials Parametersmentioning
confidence: 99%